(untitled) (Global Journal of Human-Social Science, 2023)
The COVID-19 pandemic may have destabilized the functioning of Small and Medium-sized Enterprises SMEs in particular being the principal cause for their closure in almost every country worldwide Despite its specific current cause this problem is recurrent and it will continue to happen throughout history For such reason the main purpose of this research is to present a set of guidelines for implementing a Resilient Strategic Management Such procedures should help Small and Medium-Sized Companies to face situations of economic crises or pandemics in the future by consolidating alternatives for preparing for or mitigating risks This work is exploratory research based on literature and documents and it uses qualitative techniques for data collection and investigation The research addresses current issues that still need to be explored in the literature consolidating the concept of resilience in the context of the recent economic and pandemic crises As a result in the analysis carried out within the chosen theoretical framework the main impacts caused by economic crises and pandemics were identified and related to sustainable actions arising from the characteristics of resilience The strategic guidelines derived from the analysis undertaken in this study can serve as a basis for SMEs to mitigate the risks threats and vulnerabilities present in economic or pandemic crisis scenarios